Probabilo Tour: Media Pembelajaran Berbasis Etnomatematika untuk Mendukung Kemampuan Pemecahan Masalah Matematika Siswa SMA - Farida Lailatus Sholehah; Tomi Listiawan (Universitas Islam Sultan Agung, 2025)
Mathematics learning at the high school level, particularly in probability, is often considered challenging because it is abstract and lacks real-world context. As a result, many students memorize formulas without understanding their applications, which makes it difficult to solve problems. To address these challenges, innovative learning media are needed that not only provide a variety of practice questions but also link local culture through an ethnomathematics approach, bridging abstract concepts with students' real-life experiences to make learning more meaningful, engaging, and effective in improving problem-solving abilities. This study aims to describe the development process of Probabilo Tour, an ethnomathematics-based learning media designed to support the problem-solving abilities of high school students. The research method used is research & development, utilizing the ADDIE development model (analyze, design, develop, implement, evaluate). The trial involved expert validation and practicality testing through student response questionnaires and learning outcome tests administered to 35 10th-grade students. The results showed that Probabilo Tour obtained an average validity score of 82.94% (very valid), a student response rate of 84.5% (efficient), and a learning completion rate of 91.18% among students, with a classical average of 88 (effective). The N-gain analysis produced 0.73 (high category), indicating a significant increase in problem-solving ability. Thus, Probabilo Tour is suitable for use as an ethnomathematics-based learning medium that supports high school students' mathematical problem-solving abilities. Keywords: Learning media, Ethnomathematics, Problem Solving